INVESTIGATING THE EFFECT OF HELLOTALK ON STUDENTS’ SPEAKING SKILLS IN EFL CLASSROOMS - Fahira, Zahra; Nurul Islam, Hanifa; Tarihoran, Naf’an (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
This study examines how the HelloTalk app influences students’ speaking skills in English as a Foreign Language (EFL) class. Mobile-Assisted Language Learning (MALL) apps such as HelloTalk offer opportunities for interactive and authentic language use, given that speaking is considered one of the most challenging language skills because it requires the simultaneous use of vocabulary, grammar, pronunciation, and fluency. Many students face difficulties such as a lack of confidence, limited vocabulary, and insufficient real-world communication practice. Using a descriptive quantitative design, this study involved 22 English majors selected through purposive sampling. Data were collected via a questionnaire comprising frequency and Likert scales, multiple-choice questions, and open-ended questions. Descriptive statistics and qualitative categorization were used to analyze the data. Based on the results, most students agreed that HelloTalk improves self-confidence, communication skills, vocabulary mastery, speaking fluency, and motivation to practice English. However, most students stated that the app improves speaking skills, although the results are not immediate and depend on how often it is used. Therefore, HelloTalk is a good tool for learning English as a foreign language (EFL).